The Impact of Machine Translation Post-Editing on Translation Project Management in Spain: A Study of MTPE Implementation in Project Managers’ Workflow - Fuentes-Pérez, Irene; Sánchez-Ramos, María del Mar (HERMES - Journal of Language and Communication in Business, 2025)
The globalization of markets, coupled with digital convergence and the rapid expansion of the translation sector over the last two decades, has significantly transformed the professional translation market. Once an artisanal profession, translation has evolved into a structured industrial sector, shaped by technological advancements and the integration of machine translation post-editing (MTPE). Although MTPE is now widespread in the translation industry, its impact on translation project management (TPM) remains largely understudied—especially in terms of how project managers incorporate this service into their workflows. This study investigates how MTPE affects project managers’ practices in Spain, where research on TPM processes is limited. Through an online survey of 61 project managers, the study examined their experience with MTPE integration, focusing on service implementation, quality assurance (QA) procedures, and perceived workload changes. The findings provide insights into how project managers navigate these changes and contribute to redefining professional practices within the translation sector. Consequently, even as MTPE becomes a standard service within TPM, there is still a clear need for standardized QA procedures and specialized project manager training to manage MTPE projects effectively.